Quantum dot-based ion beam polishing method for coupled silicon carbide in-situ growth

By growing the CsPbBr3 quantum dot sacrificial layer in situ on the SiC wafer surface and combining pulse ion beam polishing technology, the problems of incomplete surface defect filling and large sacrificial layer thickness in traditional polishing technology are solved, achieving ultra-smooth treatment and efficient polishing effect of SiC surface.

CN119890029AActive Publication Date: 2025-04-25CHANGCHUN UNIV OF SCI & TECH +2

Patent Information

Application Number
CN202411727075.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-04-25
Estimated Expiration
2044-11-28

AI Technical Summary

Technical Problem

Traditional SiC surface polishing technology is difficult to effectively fill and repair microcracks and micro-nano scratches on the wafer surface, resulting in high surface roughness and defects after polishing, and large sacrificial layer thickness, increasing production costs.

Method used

Using a quantum dot-based ion beam polishing method for in-situ growth, CsPbBr3 quantum dots are used as a sacrificial layer, a nanoscale thickness quantum dot layer is formed on the SiC wafer surface through in-situ growth technology, deeply filling and coupling surface defects, and material removal is performed during the pulsed ion beam polishing process.

Benefits of technology

It significantly improves the flatness of the SiC surface, reduces the thickness of the sacrificial layer, improves the polishing efficiency, reduces material loss, and achieves a good fluorescent labeling effect, meeting the surface quality requirements of high-precision optical components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119890029A_ABST
    Figure CN119890029A_ABST
Patent Text Reader

Abstract

The invention discloses an ion beam polishing method for coupled silicon carbide in-situ growth based on quantum dots, and belongs to the technical field of SiC surface polishing. The preparation method of the SiC material with the quantum dot sacrificial layer grown in situ comprises the following steps: mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution; and dropwise adding the CsPbBr3 precursor solution to the surface of the SiC material, flattening, heating for crystallization, and annealing to obtain the SiC material with the quantum dot sacrificial layer grown in situ. According to the ion beam polishing method based on quantum dot coupling silicon carbide in-situ growth, the quantum dot layer serves as the sacrificial layer of the SiC wafer, the thickness of the sacrificial layer can be effectively reduced, the flatness of the SiC surface can be remarkably improved, and the good fluorescence labeling effect can be achieved. The CsPbBr3 quantum dot prepared by the method has extremely small nano size, can deeply fill micro cracks and micro-nano scratches on the surface of a SiC wafer, is completely coupled with the micro cracks on the surface of the SiC wafer, and realizes accurate filling of defects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of SiC surface polishing, and in particular to an ion beam polishing method based on quantum dot-coupled silicon carbide in-situ growth. Background Art

[0002] Single crystal silicon carbide (SiC) has become the main research direction in the third generation semiconductor materials due to its remarkable physical and mechanical properties, such as wide band gap, high thermal conductivity, excellent stiffness, low thermal expansion coefficient and excellent wear resistance. However, due to the high brittleness, high hardness and low fracture toughness of SiC, it is difficult to maintain a high-quality smooth surface during processing. These problems easily lead to an increase in the surface roughness of SiC materials and the generation of microcracks, which in turn have a negative impact on the final application performance. Therefore, in the processing of SiC, ultra-smooth surface polishing technology is crucial.

[0003] Traditional surface polishing processes are mainly based on chemical mechanical polishing (CMP) technology. CMP technology is mainly based on mechanical grinding, using small-size hard abrasives to ductilely remove the wafer surface to remove the residual stress layer and mechanical damage layer during the grinding process, thereby achieving the purpose of improving surface flatness and surface quality. The polishing liquid is mainly composed of abrasives such as aluminum oxide (Al2O3), silicon dioxide (SiO2) and cerium dioxide (CeO2), and oxidants such as potassium permanganate (KMnO4) and hydrogen peroxide (H2O2). The surface defects are removed and the surface is flattened simultaneously with the oxidation reaction and mechanical removal. However, due to the mechanical grinding effect, the CMP process easily introduces new damage layers, resulting in defects such as scratches, pits, sub-surface microcracks and abrasive residues. The existence of these defects directly affects the yield and optoelectronic performance of the final product. Moreover, on the one hand, the CMP process requires strict control of material loss during the processing, which usually needs to be kept within 10% of the thickness of the entire device. This means that CMP must not only effectively remove excess material, but also accurately control the removal rate and the final surface effect, which places extremely high demands on the accuracy of the CMP process. On the other hand, the CMP process involves consumables such as polishing heads, polishing pads, polishing discs and repairers, which further increases production costs.

[0004] Pulsed ion beam technology uses the physical sputtering effect to bombard the surface of optical components with high-energy ion beams to remove materials at the atomic level. Compared with traditional polishing methods, the pulsed ion beam process is less affected by the chemical properties and hardness of the material, and can efficiently polish complex free-form surfaces without causing surface layer damage. In the traditional pulsed ion beam polishing process, a layer of sacrificial layer material is usually coated on the wafer surface by coating or sputtering. The sacrificial layer is used to fill surface defects before polishing to provide a smooth substrate. However, due to its physical properties, the existing sacrificial layer materials are usually difficult to completely fill and couple into the microcracks and micro-nano scratches on the surface of SiC wafers; in the pulsed ion beam polishing process, incomplete filling of the sacrificial layer material may lead to further expansion of the defect area, and even cause new surface damage when removing the material, making it difficult to effectively guarantee the flatness and surface quality of the polished wafer. Moreover, the typical thickness of the sacrificial layer is usually more than 1μm, which will greatly increase the time for removing materials and increase production costs in pulsed ion beam polishing. In summary, there are many shortcomings in traditional sacrificial layer materials. How to improve polishing efficiency and reduce material loss are urgent problems to be solved. Summary of the invention

[0005] The purpose of the present invention is to provide an ion beam polishing method based on quantum dot coupled silicon carbide in-situ growth to solve the above-mentioned problems in the background technology. The present invention proposes an ion beam polishing method based on quantum dot coupled silicon carbide in-situ growth, using the quantum dot layer as a sacrificial layer of the SiC wafer, which can not only effectively reduce the thickness of the sacrificial layer and significantly improve the flatness of the SiC surface, but also achieve a good fluorescent labeling effect. The CsPbBr3 quantum dots prepared by the present invention have extremely small nanometer sizes, can deeply fill the microcracks and micro-nano scratches on the surface of the SiC wafer, and are completely coupled with the microcracks on the surface of the SiC wafer to achieve accurate filling of defects.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] One of the technical solutions of the present invention is to provide a method for preparing a SiC material having an in-situ grown quantum dot sacrificial layer, comprising the following steps:

[0008] (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution;

[0009] (2) dropping the CsPbBr3 precursor solution onto the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown quantum dot sacrificial layer.

[0010] Preferably, the lead source is PbBr2; the cesium source is CsBr; and the molar ratio of the lead source to the cesium source is 0.9-1.1.

[0011] Preferably, the solvent is polymethyl methacrylate and / or N,N-dimethylformamide.

[0012] Preferably, the temperature of the crystallization is 70-100°C and the time is 1-2 minutes.

[0013] Preferably, the annealing temperature is 40-110° C. and the time is 1-5 min.

[0014] The second technical solution of the present invention is to provide a SiC material having an in-situ grown quantum dot sacrificial layer obtained according to the above preparation method.

[0015] The third technical solution of the present invention is to provide a polishing method for the SiC material of the above-mentioned in-situ grown quantum dot sacrificial layer, comprising the following steps:

[0016] In an Ar gas atmosphere, the SiC material having the quantum dot sacrificial layer grown in situ is subjected to pulsed ion beam polishing to obtain a polished SiC material.

[0017] Preferably, the parameters of the pulsed ion beam polishing are: ion beam rate power 110W, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow rate 20SCCM, and polishing time 1-2min.

[0018] Under the pulse ion beam polishing parameters defined in the present invention, a polishing rate of 0.17 μm / min can be achieved.

[0019] Technical solution four of the present invention: provides an optimization method for silicon carbide ion beam polishing, in situ growing a CsPbBr3 quantum dot sacrificial layer on the silicon carbide surface, and then performing pulsed ion beam polishing.

[0020] The fifth technical solution of the present invention: provides an application of CsPbBr3 quantum dots as a polishing sacrificial layer for SiC materials.

[0021] The technical principles of the present invention are as follows:

[0022] Pulsed ion beam polishing stage: The present invention places the SiC material with the in-situ grown CsPbBr3 quantum dot sacrificial layer on the ion beam etcher, firstly introduces argon (Ar) into the etching chamber, ionizes it through the ion source to generate argon ions, and forms a high-density plasma; then accelerates and focuses the ion beam through the three-grid ion optical system, so that the ion beam can act accurately on the wafer surface; then, the accelerating electric field is used to excite the ion beam to remove the sacrificial layer on the wafer surface. In each pulse cycle, the Ar in the plasma +Under the action of the accelerating electric field, the Ar + The bombardment can not only remove excess material from the surface, but also repair microscopic defects, making the wafer surface smoother at the atomic scale. Finally, after multiple pulsed plasma beams, the SiC wafer surface achieves an ultra-smooth effect with low surface roughness, meeting the surface quality requirements of high-precision optical components. Compared with traditional polishing methods, pulsed plasma beam technology can achieve efficient and fine surface smoothing without introducing surface damage.

[0023] The purpose of the annealing treatment defined in the present invention is to promote the further crystallization and growth of CsPbBr3 quantum dots, while further enhancing the coupling strength between the quantum dots and the substrate and improving the polishing quality.

[0024] The beneficial technical effects of the present invention are as follows:

[0025] The present invention proposes an ion beam polishing method based on quantum dot-coupled silicon carbide in-situ growth, which uses the quantum dot layer as a sacrificial layer of the SiC wafer, which can not only effectively reduce the thickness of the sacrificial layer and significantly improve the flatness of the SiC surface, but also achieve a good fluorescent marking effect.

[0026] The present invention selects CsPbBr3 quantum dot composite film as the sacrificial layer of SiC material, mainly because the unique advantages of the prepared CsPbBr3 quantum dot sacrificial layer in terms of size, fluorescence efficiency and coupling with the substrate are found. The CsPbBr3 quantum dots prepared by the present invention have extremely small nanometer sizes, can deeply fill the microcracks and micro-nano scratches on the surface of the SiC wafer, and are completely coupled with the microcracks on the surface of the SiC wafer to achieve accurate filling of defects. At the same time, the high fluorescence efficiency of these quantum dots ensures that a clear and bright fluorescent signal can be generated during the detection process, thereby effectively marking the defects. Under the polishing parameters defined by the present invention, the etching rate of the prepared sacrificial layer is close to that of the SiC substrate material, so the smooth surface covered with the sacrificial layer can be transferred to the surface of the SiC substrate. In addition, the CsPbBr3 quantum dots can achieve uniform distribution at nanometer scale on the wafer surface by in-situ growth, and the quantum dot layer can achieve a nanometer-level thickness due to the small size of the quantum dots. Compared with the traditional sacrificial layer (1μm), the quantum dots as a sacrificial layer effectively reduce the thickness of the sacrificial layer, achieving the purpose of wafer flattening. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0028] Figure 1 Schematic diagram of the pulsed ion beam polishing process of Example 1. (a) is a SiC surface with defects, (b) is a SiC surface after in-situ growth of a quantum dot sacrificial layer, (c) is the ion beam polishing process, and (d) is an ultra-smooth SiC surface after polishing.

[0029] Figure 2 The film thickness curve and fluorescence effect diagram of the SiC material with the in-situ growth of the CsPbBr3 quantum dot sacrificial layer in Example 1. Among them, (a) is the film thickness curve, and (b) is the fluorescence effect diagram.

[0030] Figure 3 The film thickness curve and fluorescence effect diagram of the SiC material to be polished in Comparative Example 2. Among them, (a) is the film thickness curve, (b) is the actual image under natural light, and (c) is the actual image under ultraviolet light.

[0031] Figure 4 The surface defect detection effect diagram of the SiC material with the in-situ growth of the CsPbBr3 quantum dot sacrificial layer before and after ultraviolet light excitation in Example 1. Among them, (a) is before excitation, and (b) is after excitation.

[0032] Figure 5 The surface morphology of the wafer before and after polishing of Comparative Example 3. Among them, (a) is the SiC wafer substrate, and (b) is the SiC material after polishing.

[0033] Figure 6 The wafer surface morphology before and after polishing of Example 1. Among them, (a) is a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer, and (b) is a SiC material after polishing.

[0034] Figure 7 The wafer surface morphology before and after polishing of Comparative Example 4. Among them, (a) is the wafer surface morphology before polishing, (b) is the wafer surface morphology after polishing, (c) is the three-dimensional morphology before polishing, and (d) is the three-dimensional morphology after polishing.

[0035] Figure 8 The wafer surface morphology images before and after polishing of Comparative Example 2. Among them, (a) is the wafer surface morphology image before polishing, (b) is the wafer surface morphology image after polishing, and (c) is the three-dimensional morphology image after polishing. DETAILED DESCRIPTION

[0036] Now, various exemplary embodiments of the present invention are described in detail, and this detailed description should not be considered as a limitation of the present invention, but should be understood as a more detailed description of certain aspects, characteristics and embodiments of the present invention. It should be understood that the terms described in the present invention are only for describing specific embodiments and are not used to limit the present invention.

[0037] In addition, for the numerical range in the present invention, it is understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0038] Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by those skilled in the art to which the invention pertains. Although only preferred methods and materials are described herein, any methods and materials similar or equivalent to those described herein may also be used in the practice or testing of the present invention.

[0039] The words “include,” “including,” “have,” “contain,” etc. used in the present invention are open-ended terms, meaning including but not limited to.

[0040] The present invention discloses a method for preparing a SiC material having an in-situ grown quantum dot sacrificial layer, comprising the following steps:

[0041] (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution;

[0042] (2) dropping the CsPbBr3 precursor solution onto the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown quantum dot sacrificial layer.

[0043] Preferably, the step (1) is specifically:

[0044] In a nitrogen environment, 1 g of polymethyl methacrylate (PMMA) and 2-4 mL of N,N-dimethylformamide (DMF) were mixed, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 100-130° C. The speed of the magnetic stirring was adjusted to 1500-1800 rpm, and the mixture was stirred for 1-3 h until a transparent solution was formed, thereby obtaining a PMMA / DMF solution;

[0045] In a nitrogen environment, 1.267 g of PbBr2 (lead bromide) and 0.514 g of CsBr (cesium bromide) powder were taken in 40 mL glass bottles, 4-6 mL of DMF were added, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 50-80 ° C, and the speed of the magnetic stirring was adjusted to 1000-1500 rpm. Stir overnight, and then filter through a 0.22 μm syringe filter to obtain CsBr / DMF solution and PbBr2 / DMF solution respectively;

[0046] In a nitrogen environment, the CsBr / DMF solution and the PMMA / DMF solution are mixed, and a magnetic bar is put into the mixture, placed on a heating plate, the temperature of the heating plate is adjusted to 80-100°C, the speed of the magnetic stirring is adjusted to 1500-1800rpm, and the mixture is stirred for 10-12h to obtain an intermediate solution; then the PbBr2 / DMF solution and the intermediate solution are mixed at a PbBr2:CsBr molar ratio of 2:3, and the mixture is heated and stirred at a temperature of 80-100°C and a speed of 1500-1800rpm for 10-12h to obtain the CsPbBr3 precursor solution.

[0047] Preferably, the step (2) is specifically:

[0048] After preheating the CsPbBr3 precursor solution to 70-100°C, add it dropwise onto the cleaned SiC wafer substrate, use a coating machine to spin coat it at a speed of 1000-2000rpm for 20-40s, then place it on a heating plate at 70-100°C to promote in-situ nucleation and crystallization of CsPbBr3 quantum dots, and then anneal it at 40-110°C for 1-5min to obtain a SiC material with an in-situ grown quantum dot sacrificial layer (CsPbBr3 quantum dot composite film).

[0049] Unless otherwise specified, "overnight" in the present invention is calculated as 12 hours.

[0050] All raw materials used in the following examples and comparative examples of the present invention are commercially available products.

[0051] Example 1

[0052] The preparation method of SiC material with in-situ growth of quantum dot sacrificial layer and the polishing method thereof are as follows:

[0053] (1) Preparation of CsPbBr3 precursor solution:

[0054] In a glove box with a nitrogen environment, 1 g of PMMA and 4 mL of DMF were mixed, and a magnetic stirrer was placed on a heating plate. The temperature of the heating plate was set to 100 °C, and the speed of the magnetic stirrer was adjusted to 1600 rpm. The mixture was stirred for 1 h until a transparent solution was formed, thereby obtaining a PMMA / DMF solution.

[0055] In a glove box under nitrogen environment, 1.267 g of PbBr2 and 0.514 g of CsBr powder were taken into 40 mL glass bottles, 5 mL of DMF was added, and a magnetic bar was placed on a heating plate. The temperature of the heating plate was set to 50 ° C, and the speed of the magnetic stirring was adjusted to 1300 rpm. Stir overnight, and then filter through a 0.22 μm syringe filter to obtain CsBr / DMF solution and PbBr2 / DMF solution respectively;

[0056] In a glove box with a nitrogen environment, CsBr / DMF solution and PMMA / DMF solution were mixed in a volume ratio of 3:40, and a magnetic bar was put into the mixture and placed on a heating plate. The temperature of the heating plate was adjusted to 90°C, the speed of the magnetic stirring was adjusted to 1600 rpm, and the mixture was stirred for 10 hours to obtain an intermediate solution. Then, the PbBr2 / DMF solution was mixed with the intermediate solution (the molar ratio of the Pb element in the PbBr2 / DMF solution to the Cs element in the intermediate solution was 0.9), and the mixture was heated and stirred at 90°C and 1600 rpm for 10 hours to obtain a CsPbBr3 precursor solution.

[0057] (2) Preparation of CsPbBr3 quantum dot composite film:

[0058] After preheating the above CsPbBr3 precursor solution to 80°C, add it dropwise onto the cleaned SiC wafer substrate ( Figure 1 The SiC material (a) was obtained by spin coating at 2000 rpm for 30 seconds using a coating machine, and then placed on a heating plate at 100°C for 1 minute, and then annealed at 80°C for 3 minutes to obtain a SiC material ( Figure 1 (b) in the figure.

[0059] (3) Polishing the SiC material with the quantum dot sacrificial layer grown in situ, the steps are as follows:

[0060] 1. Clean the finished product with an air gun to ensure that it is free of dust and other contaminants, then install the workpiece on a high-precision processing platform and ensure that its position is fixed.

[0061] 2. Set the ion beam polishing parameters: ion beam rate power 110W, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow 20SCCM, polishing rate 0.17μm / min. Set the scanning mode of the polishing process to rectangular coordinate mode.

[0062] 3. Start the vacuum pump to ensure that the polishing process is carried out in a high vacuum environment to avoid collision between the ion beam and air molecules and reduce energy loss.

[0063] 4. Start the ion source to generate an ion beam. The ion beam used is Ar + source.

[0064] 5. Start the polishing process and set the polishing time to 1.2min ( Figure 1 (c) in the figure.

[0065] 6. After polishing, restore the working environment to normal state and obtain the polished SiC material ( Figure 1 (d) in the figure.

[0066] Figure 1 Schematic diagram of the pulsed ion beam polishing process of Example 1. (a) is a SiC surface with defects, (b) is a SiC surface after in-situ growth of a quantum dot sacrificial layer, (c) is the ion beam polishing process, and (d) is an ultra-smooth SiC surface after polishing.

[0067] Comparative Example 1

[0068] The only difference from Example 1 is that the polishing process in step (3) is modified as follows:

[0069] 1. Clean the finished product with an air gun to ensure that it is free of dust and other contaminants, then install the workpiece on a high-precision processing platform and ensure that its position is fixed.

[0070] 2. Set the ion beam polishing parameters: ion beam rate power 110W, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 25mA, neutralizer current 165mA, Ar gas flow 30SCCM, polishing rate 0.17μm / min. Set the scanning mode of the polishing process to rectangular coordinate mode.

[0071] 3. Start the vacuum pump to ensure that the polishing process is carried out in a high vacuum environment to avoid collision between the ion beam and air molecules and reduce energy loss.

[0072] 4. Start the ion source to generate an ion beam. The ion beam used is Ar + source.

[0073] 5. Start the polishing process and set the polishing time to 1.2 minutes.

[0074] 6. After polishing is completed, restore the working environment to normal state to obtain the polished SiC material.

[0075] Comparative Example 2

[0076] The only difference from Example 1 is that step (2) is modified to:

[0077] SU-8 photoresist was dropped onto the cleaned SiC wafer substrate, and spin-coated at 2000 rpm for 30 seconds using a coating machine, and then annealed on a hot plate at 80°C for 1 minute to obtain the SiC material to be polished, and then the polishing treatment of step (3) was performed.

[0078] Comparative Example 3

[0079] The only difference from Example 1 is that the in-situ growth of the quantum dot sacrificial layer is omitted, and the SiC wafer substrate cleaned in step (2) is directly polished.

[0080] Comparative Example 4

[0081] The only difference from Example 1 is that the SiC wafer substrate in step (2) is modified to a rough-ground SiC wafer substrate. The preparation method of the rough-ground SiC wafer substrate is:

[0082] Boron carbide powder with a particle size of 50 μm is used as an abrasive and mixed with water to form a grinding liquid (boron carbide powder accounts for 30% of the grinding liquid). The SiC wafer substrate is fixed on the grinding disk and the pressure is 3 kg / cm 2 The grinding was carried out at a speed of 500 rpm to obtain a roughly ground SiC wafer substrate.

[0083] The purpose of the rough grinding is to verify the polishing effect of the polishing method of the present invention on samples with high roughness (more and larger scratches and defects).

[0084] Effect verification

[0085] 1. The sacrificial layer and photoluminescence effect of the SiC material with in-situ quantum dot sacrificial layer grown in Example 1 and Comparative Example 2 were characterized; the wavelength of the ultraviolet light used in the photoluminescence effect test was 365nm. The test results are as follows Figure 2-3 shown.

[0086] The fluctuation of the film thickness curve can represent the roughness of the film. The greater the fluctuation, the greater the roughness, and the flatter the curve, the smaller the roughness.

[0087] Figure 2 The film thickness curve and fluorescence effect diagram of the SiC material with the in-situ growth of the CsPbBr3 quantum dot sacrificial layer in Example 1. Among them, (a) is the film thickness curve, and (b) is the fluorescence effect diagram.

[0088] Depend on Figure 2 It can be seen that the quantum dot sacrificial layer prepared in Example 1 has a thickness of about 187 nm and has bright fluorescence intensity.

[0089] Figure 3The film thickness curve and fluorescence effect diagram of the SiC material to be polished in Comparative Example 2. Among them, (a) is the film thickness curve, (b) is the actual image under natural light, and (c) is the actual image under ultraviolet light.

[0090] Depend on Figure 3 It can be seen that the thickness of the sacrificial layer in Comparative Example 2 is about 188 nm, which is almost 5 times that of Example 1; and the SiC material to be polished in Comparative Example 2 has no fluorescence effect, and therefore has no defect marking function.

[0091] 2. Surface defect detection of materials after UV light excitation. Test results are as follows: Figure 4 shown.

[0092] Figure 4 The surface defect detection effect diagram of the SiC material with the in-situ growth of the CsPbBr3 quantum dot sacrificial layer before and after ultraviolet light excitation in Example 1. Among them, (a) is before excitation, and (b) is after excitation.

[0093] Figure 4 In the figure, the purple frame marks the pit defect on the surface of the material, and the red frame marks the surface defect that is invisible under white light. As can be seen from the figure, the CsPbBr3 quantum dot composite film can achieve effective fluorescent marking of defects after being excited by ultraviolet light, thereby achieving the purpose of defect detection.

[0094] 3. In order to characterize the surface roughness of the wafer after ion beam polishing, a white light interferometer was used to characterize the surface roughness of the polished SiC material in Example 1 and Comparative Examples 1-2 to evaluate the polishing effect. The characterization method is as follows:

[0095] (1) Clean the polished SiC material surface to prevent oil, fingerprints or other contaminants from affecting the measurement results.

[0096] (2) A Zygo NewView 700s white light interferometer was used to perform micrometer-scale medium and high frequency detection on the wafer surface, with magnifications of 10x and 50x, respectively. The detection range was 468μm×351μm, and the data resolutions were 1.5μm and 7.5μm, respectively.

[0097] (3) Place the SiC wafer on the interferometer measurement table and adjust the optical focal length until the workpiece surface is clearly visible.

[0098] (4) Randomly test two points on the SiC wafer, calculate the surface roughness parameters and reconstruct the three-dimensional surface shape.

[0099] Figure 5 The surface morphology of the wafer before and after polishing of Comparative Example 3. Among them, (a) is the SiC wafer substrate, and (b) is the SiC material after polishing.

[0100] Figure 6 The wafer surface morphology before and after polishing of Example 1. Among them, (a) is a SiC material with an in-situ grown CsPbBr3 quantum dot sacrificial layer, and (b) is a SiC material after polishing.

[0101] Figure 7 The wafer surface morphology before and after polishing of Comparative Example 4. Among them, (a) is the wafer surface morphology before polishing, (b) is the wafer surface morphology after polishing, (c) is the three-dimensional morphology before polishing, and (d) is the three-dimensional morphology after polishing.

[0102] Figure 8 The wafer surface morphology before and after polishing of Comparative Example 2. Among them, (a) is the wafer surface morphology before polishing, (b) is the wafer surface morphology after polishing, and (c) is the three-dimensional morphology after polishing.

[0103] Figure 5 It can be seen that without in-situ generation of quantum dot sacrificial layer, the surface roughness of SiC wafer substrate before polishing is 2.472nm, and after pulsed ion beam polishing, the surface roughness increases significantly to 8.622nm. In contrast, after adding CsPbBr3 quantum dots as sacrificial layer, the surface roughness of SiC after polishing is reduced to 1.505nm (see Figure 6 ), the surface roughness was reduced by nearly 573%.

[0104] Figure 7 It can be seen that after ion beam polishing, the scratches on the material surface are effectively reduced, and the surface roughness is reduced by nearly 1 times. The experimental results show that the quantum dots of the present invention can significantly improve the flatness of the SiC surface as a sacrificial layer.

[0105] Figure 8 It can be seen that before polishing, the surface roughness of the material is 2.121nm, while after polishing, the surface roughness increases to 517.041nm. This is mainly because the sacrificial layer material of Comparative Example 2 has large differences in thickness and uniformity, and cannot evenly cover and fill the microcracks on the wafer surface, resulting in unsatisfactory polishing effect. Therefore, after pulsed ion beam treatment, obvious burrs and irregular fluctuations appear on the wafer surface. Figure 8 This further demonstrates the superiority of the quantum dot sacrificial layer designed by the present invention in the planarization process.

[0106] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a SiC material having an in-situ grown quantum dot sacrificial layer, characterized in that: The following steps are involved: (1) mixing a lead source, a cesium source and a solvent to obtain a CsPbBr3 precursor solution; (2) dropping the CsPbBr3 precursor solution onto the surface of the SiC material, coating it flat, heating it for crystallization, and annealing it to obtain a SiC material with an in-situ grown quantum dot sacrificial layer.

2. The preparation method according to claim 1, characterized in that: The lead source is PbBr2; the cesium source is CsBr; and the molar ratio of the lead source to the cesium source is 0.9-1.

1.

3. The preparation method according to claim 1, characterized in that: The solvent is polymethyl methacrylate and / or N,N-dimethylformamide.

4. The preparation method according to claim 1, characterized in that: The temperature of the temperature-raising crystallization is 70-100° C., and the time is 1-2 minutes.

5. The preparation method according to claim 1, characterized in that: The annealing temperature is 40-110° C. and the annealing time is 1-5 min.

6. A SiC material having an in-situ grown quantum dot sacrificial layer obtained according to the preparation method according to any one of claims 1 to 5.

7. A polishing method for SiC material with in-situ growth quantum dot sacrificial layer according to claim 6, characterized in that: The following steps are involved: In an Ar gas atmosphere, the SiC material having the quantum dot sacrificial layer grown in situ is subjected to pulsed ion beam polishing to obtain a polished SiC material.

8. The method according to claim 7, characterized in that The parameters of the pulsed ion beam polishing are: ion beam rate power 110W, screen grid voltage 800V, acceleration grid voltage 110V, screen grid current 18mA, neutralizer current 158mA, Ar gas flow rate 20SCCM, and polishing time 1-2min.

9. A method for optimizing silicon carbide ion beam polishing, characterized in that: A CsPbBr3 quantum dot sacrificial layer is in-situ grown on the silicon carbide surface and then pulsed ion beam polishing is performed.

10. Application of CsPbBr3 quantum dots as a sacrificial layer for polishing SiC materials.

Citation Information

Patent Citations

  • Blue light CsPbBr3 perovskite thin film and preparation method thereof

    CN118302008A

  • Method for manufacturing silicon carbide wafer, silicon carbide wafer, silicon carbide semiconductor element, and power converting device

    JP2013107788A

  • Luminescent composite material and preparation method therefor

    US20210198568A1

Cited By

  • Efficiency-matched quantum dot nanolayer removal method and in-situ growth method and application thereof

    CN121006118A

  • Quantum dot nanolayers with removal efficiency matching, their in-situ growth methods and applications

    CN121006118B

  • Grating structure with continuous gradually-changed depth based on silicon carbide substrate and preparation method of grating structure

    CN121276675A